A plated ultra-high strength steel with low spot weld crack sensitivity and a method of manufacturing the same
Patent Information
- Application Number
- CN202211168303.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-23
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2042-09-23
AI Technical Summary
但是,该技术方案存在着内氧化层厚度和均匀性以及钢板表层成分分布均匀性不易控制的问题
[0072] In the coated ultra-high strength steel designed in this invention, its chemical element composition is based on C, Si, Mn, B, Al and Mo. By optimizing the ratio of each element, coated ultra-high strength steel with low sensitivity to spot weld cracks can be obtained.
Smart Images

Figure CN117802400B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a high-strength steel and its manufacturing method, and more particularly to a coated ultra-high-strength steel and its manufacturing method. Background Technology
[0002] Currently, with the advancement of automotive lightweighting and the increasing demands for corrosion resistance in the automotive industry, many automakers are placing greater emphasis on coated ultra-high-strength steel. For cold-stamped steel, the coating is primarily zinc-containing, such as hot-dip pure zinc, hot-dip galvanized iron, and electroplated pure zinc. Resistance spot welding, due to its advantages of high welding speed and low cost, has become the most important joining method in automotive welding production. Many zinc-coated ultra-high-strength steel joints often exhibit good quasi-static mechanical properties during spot welding; however, a type of welding crack appears on the surface of the steel plate in contact with the electrode and in the vicinity. This welding crack is called a spot weld crack. Figure 1 The diagram illustrates a spot weld crack in ultra-high strength steel with a zinc coating. However, suppressing the formation of such cracks is extremely difficult, making it a significant obstacle and bottleneck for the application of zinc-coated ultra-high strength steel in the automotive industry.
[0003] While some existing technologies are known to control welding cracks, they still have many drawbacks:
[0004] For example, Chinese patent document CN108015401A, published on May 11, 2018, entitled "Resistance Spot Welding Method for Galvanized High-Strength Steel with Good Joint Performance", discloses a method that, through innovation in spot welding process, suppresses surface cracks of spot welds while ensuring that the performance of the weld joint is not reduced.
[0005] For example, Chinese patent document CN109385515A, published on February 26, 2019, entitled "Multilayer Steel and Method for Reducing Embrittlement of Liquid Metal", discloses a method for suppressing the generation of spot weld cracks in high-strength steel. The method suppresses the generation of spot weld cracks by first decarburizing the high-strength steel and then galvanizing it, so that the thickness of the decarburized layer is between 10 and 50 micrometers.
[0006] For example, Chinese patent document CN110892087A, published on March 17, 2020, entitled "Zinc-coated steel sheet with high resistance to spot welding," discloses a technical solution that improves the surface composition distribution by increasing the dew point to form an inner oxide layer on the steel sheet, thereby reducing the occurrence of spot weld cracks. However, this technical solution has the problem that the thickness and uniformity of the inner oxide layer, as well as the uniformity of the surface composition distribution of the steel sheet, are difficult to control. Summary of the Invention
[0007] One of the objectives of this invention is to provide a coated ultra-high strength steel with low spot weld crack sensitivity. This coated ultra-high strength steel has excellent quality and performance. While meeting the user's requirements for the performance of coated high strength steel and the mechanical properties of spot welded joints, it also has low spot weld crack sensitivity, and has good prospects for widespread application.
[0008] To achieve the above objectives, the present invention provides a coated ultra-high strength steel with low spot weld crack sensitivity, comprising a steel substrate and a zinc-containing coating on the surface of the steel substrate, wherein the steel substrate contains Fe and unavoidable impurity elements, and the steel substrate further contains the following chemical elements in the following mass percentages:
[0009] C: 0.10~0.30%; Si: 0.30~0.90%; Mn: 1.00~2.20%; B: 0.001~0.003%; Al: 0.30~1.00%.
[0010] Furthermore, in the coated ultra-high strength steel described in this invention, the mass percentage content of each chemical element in the steel substrate is as follows:
[0011] C: 0.10–0.30%; Si: 0.30–0.90%; Mn: 1.00–2.20%; B: 0.001–0.003%; Al: 0.30–1.00%; balance is Fe and unavoidable impurity elements.
[0012] Furthermore, in the coated ultra-high strength steel described in this invention, the chemical elements of the steel substrate also contain Mo: 0.10-2.00%.
[0013] In the above-mentioned technical solution of the present invention, a chemical composition design based on carbon, silicon, manganese, boron or boron-molybdenum composite is adopted, which makes full use of the role of carbon, silicon, manganese, boron and molybdenum elements in material phase transformation, thereby achieving the unity of high mechanical properties and high spot welding performance of the ultra-high strength steel described in the present invention, and finally obtaining a coated ultra-high strength steel product with low spot weld crack sensitivity.
[0014] The design principles of each chemical element in the coated ultra-high strength steel described in this invention are as follows:
[0015] C: In the coated ultra-high strength steel with low spot weld crack sensitivity described in this invention, the solubility of carbon in austenite is much higher than its solubility in ferrite. This can prolong the incubation period before austenite transformation and lower the Ms temperature. The higher the mass percentage of carbon in the steel, the greater the fraction of retained austenite, and the higher the enrichment degree of carbon in the retained austenite during partitioning. This is beneficial for enhancing the stability of retained austenite, generating the TRIP effect, and improving the ductility of the material. Furthermore, carbon is also the most basic solid solution strengthening element in steel. However, it should be noted that the carbon content in the steel should not be too high. When the mass percentage of carbon is too high, it will reduce the weldability of the steel, especially significantly increasing the tendency for surface cracks to occur at the weld joint. Based on this, in order to maximize the beneficial effects of element C, the mass percentage of element C in this invention is controlled at 0.10–0.30%.
[0016] Of course, in some preferred embodiments, in order to obtain better implementation results, the mass percentage content of element C can be further preferably controlled between 0.15% and 0.20%.
[0017] Si: In the coated ultra-high-strength steel with low spot weld crack sensitivity described in this invention, silicon has extremely low solubility in carbides. It can strongly inhibit cementite formation during the fractionation process, promote carbon enrichment in the retained austenite, and improve the stability of the retained austenite. However, it should be noted that excessive silicon should not be added to the steel. Too high a mass percentage of silicon will reduce the high-temperature plasticity of the steel and form stable oxides on the steel plate surface, reducing the wettability of the steel plate. In particular, the inventors of this invention have found that silicon is an element that significantly increases the tendency for surface cracking at weld points. Based on this, in the coated ultra-high-strength steel with low spot weld crack sensitivity described in this invention, the mass percentage of Si is specifically controlled between 0.30% and 0.90%.
[0018] Of course, in some preferred embodiments, in order to obtain better implementation results, the mass percentage content of Si element can be further preferably controlled between 0.40% and 0.80%.
[0019] Mn: In the coated ultra-high strength steel with low spot weld crack sensitivity described in this invention, manganese can expand the austenite phase region and reduce Ac3 and M s and M fManganese (Mn) enhances austenite stability and hardenability, lowers the critical transformation rate, and helps preserve residual austenite to room temperature. Simultaneously, Mn also provides solid solution strengthening in steel. However, when the Mn content is too low, segregation can lead to the formation of ferrite and pearlite banded structures at low cooling rates. Furthermore, the mass percentage of Mn in steel should not be too high. Excessive Mn content exacerbates grain coarsening, reduces plasticity and toughness, and worsens corrosion resistance. In particular, it increases manganese enrichment in the shallow surface layer of the base material under the coating, increasing the surface crack sensitivity of weld joints and deteriorating weldability. Therefore, to maximize the beneficial effects of Mn, the mass percentage of Mn in the coated ultra-high-strength steel with low spot weld crack sensitivity described in this invention is controlled at 1.00–2.20%.
[0020] Of course, in some preferred embodiments, in order to obtain better implementation results, the mass percentage content of Mn element can be further preferably controlled between 1.00% and 2.00%.
[0021] B: In the coated ultra-high strength steel with low spot weld crack sensitivity described in this invention, boron can significantly improve the hardenability of the steel. On the one hand, boron tends to segregate at grain boundaries, filling grain boundary defects and reducing grain boundary energy. This makes it more difficult for new phases to nucleate on the austenite grain boundaries, which are originally the nucleation site of ferrite, thus increasing the stability of austenite and improving hardenability. On the other hand, the addition of boron reduces the steel's need for hardenability-enhancing elements such as carbon and manganese.
[0022] Furthermore, the inventors in this case discovered that boron reduces the segregation of manganese towards grain boundaries, thereby reducing the formation of a manganese-enriched layer in the steel substrate under the coating, and thus significantly reducing the formation of spot weld cracks. However, more boron is not necessarily better. If more boron still segregates non-equilibrium after the grain boundary defects are filled, it will form a "boron phase" precipitation at the grain boundaries, increasing the grain boundary energy. At the same time, the "boron phase" will act as the nucleus of a new phase, promoting an increased nucleation rate, reducing the stability of austenite, and decreasing hardenability. In other words, significant "boron phase" precipitation has an adverse effect on hardenability, and a large amount of "boron phase" precipitation will make the steel brittle, negatively impacting its mechanical properties; moreover, embrittled grain boundaries will promote the occurrence and propagation of spot weld cracks.
[0023] The inventors of this invention discovered that a boron content of 0.0030% is the inflection point that causes grain boundary embrittlement. Based on this, to fully utilize the excellent effects of boron, the mass percentage of boron in the coated ultra-high-strength steel with low spot weld crack sensitivity described in this invention is controlled at 0.001–0.003%.
[0024] Of course, in some preferred embodiments, in order to obtain better implementation results, the mass percentage content of element B can be further preferably controlled between 0.0015% and 0.003%.
[0025] In the coated ultra-high strength steel with low spot weld crack sensitivity described in this invention, aluminum, when present in a solid solution state, can increase stacking fault energy, inhibit cementite precipitation and γ-to-martensite transformation, and improve austenite stability. Furthermore, aluminum forms fine, dispersed, insoluble particles with carbon and nitrogen, which can refine the grain size; however, aluminum's strengthening effect is weaker than silicon, and its ability to stabilize austenite is also weaker. In addition, when the mass percentage of aluminum in the steel is too high, it easily forms a large number of oxide inclusions, which is detrimental to continuous casting. Therefore, in the coated ultra-high strength steel with low spot weld crack sensitivity described in this invention, the mass percentage of Al is controlled between 0.30% and 1.00%.
[0026] Mo: In the coated ultra-high strength steel with low spot weld crack sensitivity described in this invention, molybdenum shifts the C-curve to the right and lowers the Ms point, thereby improving the hardenability of the steel and increasing its elongation while simultaneously increasing its strength. Furthermore, molybdenum is a strong carbide-forming element; during smelting, it forms fine and dispersed MoC particles, which are distributed as a hard second phase in martensite during subsequent phase transformations, thus significantly improving the steel's toughness. More importantly, the inventors have discovered that the addition of molybdenum can significantly improve the steel's resistance to spot weld cracks. Based on this, considering the above factors and the cost of adding molybdenum, the mass percentage of Mo in the coated ultra-high strength steel with low spot weld crack sensitivity described in this invention is controlled between 0.10% and 2.00%.
[0027] Of course, in some preferred embodiments, in order to obtain better implementation results, the mass percentage content of Mo element can be further preferably controlled between 0.10% and 1.00%.
[0028] Furthermore, in the coated ultra-high strength steel of the present invention, the mass percentage content of each chemical element in the steel substrate satisfies at least one of the following:
[0029] C: 0.15–0.20%;
[0030] Si: 0.40–0.80%;
[0031] Mn: 1.00~2.00%;
[0032] B: 0.0015~0.003%;
[0033] Mo: 0.10–1.00%.
[0034] Furthermore, in the coated ultra-high strength steel of the present invention, the mass percentage content of unavoidable impurity elements in the steel substrate satisfies: P≤0.01%, S≤0.005%.
[0035] In the above technical solution, P and S elements are impurity elements in the coated ultra-high strength steel of the present invention. When technical conditions permit, in order to obtain steel with better performance and higher quality, the content of impurity elements in coated ultra-high strength steel should be reduced as much as possible.
[0036] In this invention, P and S are both impurity elements. Although P can play a solid solution strengthening role, inhibit carbide formation, and help improve the stability of retained austenite, an excessively high mass percentage of P will weaken grain boundaries, increase material brittleness, and deteriorate weldability. In other words, the positive effects of P are weaker than its negative effects. Therefore, it is preferable to control the mass percentage of P to P≤0.01%.
[0037] Correspondingly, sulfur in steel tends to form low-melting eutectic at grain boundaries. When its mass percentage is too high, it will significantly deteriorate the plasticity of the material. Therefore, the mass percentage of sulfur is controlled to be S≤0.005%.
[0038] Furthermore, in the coated ultra-high strength steel described in this invention, the microstructure of the steel substrate is ferrite + martensite + retained austenite.
[0039] Furthermore, in the coated ultra-high strength steel of the present invention, the volume proportion of ferrite is 25% to 45%; and / or the volume proportion of martensite is 45% to 65%.
[0040] Furthermore, in the coated ultra-high strength steel of the present invention, the volume percentage of grains with a size of less than 10 μm in the ferrite is ≥85%, and the volume percentage of grains with a size of less than 5 μm is ≥55%.
[0041] Furthermore, in the coated ultra-high strength steel of the present invention, the average grain size of the retained austenite is ≤2μm; and / or the average C content in the retained austenite is ≥1.0%.
[0042] Furthermore, in the coated ultra-high strength steel described in this invention, when spot welding is performed, if surface cracks occur at the weld point, the maximum length of the surface crack is less than 5% of the plate thickness.
[0043] Furthermore, in the coated ultra-high strength steel described in this invention, its mechanical properties meet the following requirements: its yield strength is 600MPa~850MPa, its tensile strength is 980MPa~1150MPa, its uniform elongation is not less than 13%, and its elongation at break is not less than 15%.
[0044] Furthermore, in the coated ultra-high strength steel described in this invention, the coating is a pure zinc coating, a zinc-iron alloy coating, a zinc-aluminum-magnesium coating, or an aluminum-zinc coating.
[0045] Accordingly, another objective of the present invention is to provide a method for manufacturing coated ultra-high strength steel, which is simple to produce and the resulting high strength steel exhibits significantly improved spot welding performance, especially resistance to surface cracking at weld points, under the same mechanical properties.
[0046] To achieve the above objectives, this invention proposes a method for manufacturing coated ultra-high strength steel, which specifically includes the following steps:
[0047] (1) Smelting and thin-plate continuous casting;
[0048] (2) Heating;
[0049] (3) Hot rolling: The thickness of the oxide scale on the surface of the hot-rolled steel strip is controlled to be ≤4μm, and the mass percentage of FeO+Fe3O4 in the oxide scale on the surface of the hot-rolled steel strip is ≤50wt%.
[0050] (4) Pickling, or pickling + cold rolling;
[0051] (5) Continuous annealing: Anneal at 800-920℃, then slowly cool to 700-770℃ at a cooling rate of 3-10℃ / s; then rapidly cool to 200-300℃ at a cooling rate of 50-500℃ / s; then heat to 360-460℃ and hold for 50-600s; finally cool to room temperature.
[0052] (6) Apply a zinc-containing coating.
[0053] In the technical solution described in this invention, the manufacturing method employs a thin slab continuous casting process combined with pickling or pickling rolling, followed by continuous annealing and coating, to obtain coated ultra-high-strength steel with low sensitivity to spot weld cracks. The coated ultra-high-strength steel produced by this method can be welded using conventional spot welding processes in automotive manufacturing, and the maximum length of surface cracks at the weld points is less than 5% of the plate thickness. It exhibits very low sensitivity to spot weld cracks and demonstrates excellent quality.
[0054] In step (1) of the present invention, since thin slab continuous casting is used, the rough rolling process can be omitted, the hot rolling deformation can be reduced, and the steel plate performance in subsequent steps (4) and (5) can be guaranteed. In addition, since thin slab continuous casting is used in step (1), the heat of the slab can be fully utilized, the energy consumption required for heating can be reduced, and a more uniform ferrite or ferrite + pearlite structure can be obtained. This is beneficial to maintaining a certain amount of fine-grained ferrite in the microstructure of the substrate of the finished product in step (6) and improving the uniformity of the structure.
[0055] In step (2), controlling the thickness of the oxide scale on the surface of the hot-rolled steel strip to be ≤4μm and the (FeO+Fe3O4) content in the oxide scale to be ≤50wt% is beneficial to the subsequent process in step (4) and has an important impact on the properties of the steel plate obtained after continuous annealing. This is because: in the technical solution described in this invention, FeO and Fe3O4 are more difficult to pickle than Fe2O3. Controlling the thickness of the oxide scale on the surface of the hot-rolled steel strip prepared in this invention and the (FeO+Fe3O4) content in the oxide scale to be ≤50wt% can effectively improve the pickling effect and obtain a pickled plate surface that can be used for direct continuous annealing. Since the pickled plate can be directly subjected to continuous annealing, the deformation of the hot-rolled structure is small, and the steel plate structure is mainly composed of pearlite and ferrite. Therefore, under the same continuous annealing conditions, the material strength can be reduced, making the structure more uniform and thus obtaining excellent ductility.
[0056] Accordingly, in step (5), the inventors optimized the continuous annealing process by controlling the annealing temperature to 800–920°C to form a homogeneous austenitic or austenitic + ferrite structure; then, the temperature was slowly cooled to 700–770°C at a cooling rate of 3–10°C / s to further adjust the ferrite content in the structure and obtain a certain proportion of ferrite, thereby improving the plasticity of the material; then, the temperature was cooled again to 200–300°C at a rate of 50–500°C / s (i.e., between M... s (The onset temperature of martensitic transformation) and M f (between the martensitic transformation completion temperature) At this point, austenite partially transforms into martensite, which ensures that the steel obtains high strength; then, heating to 360-460℃ and holding for 50-600s allows carbon to be distributed in the martensite and austenite, forming a certain amount of carbon-rich residual austenite, which is then stably maintained at room temperature. Due to the TRIP effect, the work hardening ability and formability of the steel can be significantly improved, resulting in high-strength steel plates with excellent ductility.
[0057] Furthermore, given the inventors' understanding of the influence of carbon, silicon, manganese, boron, or boron-molybdenum on spot weld cracks, especially the understanding that silicon and manganese tend to accumulate in the shallow surface layer of steel plates, significantly increasing the sensitivity of weld surface cracks, this invention, in addition to strictly limiting the content of carbon, silicon, manganese, boron, or boron-molybdenum in the steel composition design, also reduces the content of carbon, silicon, and manganese elements compared to steel of the same strength level, and adds boron and molybdenum elements to increase the hardenability of the steel. This ensures that the required microstructure composition is obtained in step (5), and guarantees that the ultra-high strength steel with zinc coating obtained after step (6) has low spot weld crack sensitivity, that is, the maximum length of the surface crack of the weld is less than 5% of the plate thickness.
[0058] It should be noted that when plating the zinc-containing coating in step (6), the zinc-containing coating can be obtained by hot-dip galvanizing, electroplating, or vacuum plating techniques, but is not limited to these methods.
[0059] In summary, the coated ultra-high-strength steel designed in this invention employs a chemical composition of carbon, silicon, manganese, boron, aluminum, and molybdenum, combined with ferrite grain refinement. Therefore, during continuous annealing, while increasing the nucleation sites for the austenite inverse transformation, it further refines the grain size, thus maintaining a stable average grain size of retained austenite ≤2μm at room temperature; and an average C content ≥1.0% in the retained austenite.
[0060] Furthermore, in the manufacturing method of coated ultra-high strength steel described in this invention, in step (1), the slab thickness at the exit end of the thin strip continuous casting is controlled to be 50-58 mm.
[0061] Furthermore, in the manufacturing method of coated ultra-high strength steel described in this invention, in step (1), the casting speed of the thin strip is controlled to be 2 to 5 m / min.
[0062] Furthermore, in the manufacturing method of coated ultra-high strength steel according to the present invention, in step (2), the slab is heated to 1200-1250°C.
[0063] Furthermore, in the manufacturing method of coated ultra-high strength steel according to the present invention, in step (3), the final rolling temperature is controlled to be 860-930°C and the coiling temperature is controlled to be 450-600°C.
[0064] Furthermore, in the manufacturing method of coated ultra-high strength steel described in this invention, in step (4), when pickling + cold rolling is used, the cold rolling deformation is controlled to be 40% to 60%.
[0065] Furthermore, in the manufacturing method of coated ultra-high strength steel according to the present invention, in step (5), the volume content of hydrogen in the reducing atmosphere in the continuous annealing furnace is controlled to be 10-15%.
[0066] Furthermore, in the manufacturing method of coated ultra-high strength steel according to the present invention, the annealing process parameters in step (5) satisfy at least one of the following:
[0067] The annealing temperature is 820–870℃;
[0068] Slowly cool to 700-730℃ at a cooling rate of 3-10℃ / s;
[0069] Cool quickly to 250-300℃;
[0070] Cool quickly and then reheat to 400-430℃, hold for 180-300 seconds.
[0071] Compared with existing technologies, the low spot weld crack sensitivity coated ultra-high strength steel and its manufacturing method described in this invention have the following advantages and beneficial effects:
[0072] In the coated ultra-high strength steel designed in this invention, its chemical element composition is based on C, Si, Mn, B, Al and Mo. By optimizing the ratio of each element, coated ultra-high strength steel with low sensitivity to spot weld cracks can be obtained.
[0073] The coated ultra-high strength steel with low spot weld crack sensitivity described in this invention has excellent quality and performance. While meeting the user's requirements for the performance of coated high strength steel and the mechanical properties of spot welded joints, it also has low spot weld crack sensitivity.
[0074] The coated ultra-high strength steel prepared using this technical solution of the present invention includes a steel substrate and a zinc-containing coating on the surface of the steel substrate. Its mechanical properties meet the following requirements: its yield strength is 600MPa to 850MPa, its tensile strength is 980MPa to 1150MPa, its uniform elongation is not less than 13%, and its elongation at break is not less than 15%. Furthermore, when spot welding is actually performed, if surface cracks occur at the weld point, the maximum length of the surface crack is less than 5% of the plate thickness.
[0075] The manufacturing method designed in this invention has a simple production process, and the high-strength steel obtained has significantly improved resistance to spot weld cracks under the same mechanical properties, which will have good application prospects in the production of safety structural components for downstream users. Attached Figure Description
[0076] Figure 1 A schematic diagram of spot weld cracks in ultra-high strength steel with zinc coating is shown. Detailed Implementation
[0077] The following will further explain and illustrate the low spot weld crack sensitivity coated ultra-high strength steel and its manufacturing method described in this invention with reference to specific embodiments. However, this explanation and illustration do not constitute an undue limitation on the technical solution of this invention.
[0078] Examples 1-28 and Comparative Examples 1-4
[0079] The coated ultra-high strength steel of Examples 1-28 and the comparative steel of Comparative Examples 1-4 described in this invention were all prepared using the following steps:
[0080] (1) Smelting and thin plate continuous casting are carried out according to the chemical composition ratio designed in Table 1. The thickness of the slab at the exit end of the thin strip continuous casting is controlled to be 50-58 mm, and the casting speed of the thin strip continuous casting is controlled to be 2-5 m / min, so as to obtain the corresponding slab.
[0081] (2) Heating: Heat the slab to 1200-1250℃.
[0082] (3) Hot rolling: The thickness of the oxide scale on the surface of the hot-rolled steel strip is controlled to be ≤4μm, and the (FeO+Fe3O4) in the oxide scale on the surface of the hot-rolled steel strip is ≤50wt%. The final rolling temperature is controlled to be 860~930℃ and the coiling temperature is controlled to be 450~600℃.
[0083] (4) Pickling, or pickling + cold rolling. When pickling + cold rolling is used, the cold rolling deformation is controlled to be 40% to 60%. When galvanizing or zinc alloy plating is performed directly after pickling, the cold rolling deformation in Table 2-2 is 0.
[0084] (5) Continuous annealing: The volume content of hydrogen in the reducing atmosphere in the continuous annealing furnace is controlled to be 10-15%; annealing is carried out at 800-920℃, preferably 820-870℃, and then slowly cooled to 700-770℃ at a cooling rate of 3-10℃ / s to obtain a certain proportion of ferrite. The final cooling temperature can preferably be controlled between 700-730℃; then rapidly cooled to 200-300℃ at a cooling rate of 50-500℃ / s to transform the austenite portion into martensite. The final cooling temperature can preferably be controlled between 250-300℃; then rapidly cooled and reheated to 360-460℃, preferably 400-430℃, and held for 50-600s, preferably 180-300s; finally cooled to room temperature.
[0085] (6) The coating is made of zinc or zinc alloy, and the coating may be specifically selected as pure zinc coating, zinc-iron alloy coating, zinc-aluminum-magnesium coating or aluminum-zinc coating.
[0086] It should be noted that, in this invention, the chemical composition design and related manufacturing processes used in the coated ultra-high strength steel of Examples 1-28 all meet the specifications designed in this invention. Correspondingly, the chemical composition design and related manufacturing processes used in the comparative steels of Comparative Examples 1-4 all contain process parameters that do not meet the design requirements of this invention.
[0087] Table 1 lists the mass percentage of each chemical element in the steel plate substrates of the coated ultra-high strength steel of Examples 1-28 and the comparative steel of Comparative Examples 1-4.
[0088] Table 1. (wt%, balance Fe and other unavoidable impurities besides P and S)
[0089]
[0090]
[0091] Accordingly, Tables 2-1 and 2-2 list the specific process parameters of the coated ultra-high strength steel of Examples 1-28 and the comparative steel of Comparative Examples 1-4 in the above process steps (1)-(6).
[0092] Table 2-1.
[0093]
[0094]
[0095] Note: In Table 2-1 above, "(FeO+Fe3O4) percentage" indicates the mass percentage of FeO and Fe3O4 in the oxide scale on the surface of the hot-rolled strip.
[0096] Table 2-2.
[0097]
[0098]
[0099] It should be noted that, before performing the plating process in step (6) above, in order to verify the excellent performance of the coated ultra-high strength steel of Examples 1-28, the inventors took samples of the coated ultra-high strength steel substrates of Examples 1-28 and the comparative steel substrates of Comparative Examples 1-4 obtained after the continuous annealing process in step (5), and observed the microstructure of the substrates of each example and comparative example. At the same time, the mechanical properties of the substrates of each example and comparative example were tested. The microstructure observation results of the substrates of each example and comparative example are listed in Table 3 below, and the mechanical property test results of the substrates of each example and comparative example are listed in Table 4 below.
[0100] Table 3 lists the microstructure observation results of the coated ultra-high strength steel substrates of Examples 1-28 and the comparative steel substrates of Comparative Examples 1-4.
[0101] Table 3.
[0102]
[0103]
[0104] Accordingly, when conducting mechanical property tests on the substrates of each embodiment and comparative example, the relevant mechanical property testing methods are as follows:
[0105] Tensile property testing: Tensile tests were conducted according to GB / T228.1-2010 Metallic materials, tensile testing - Part 1: Tests at room temperature, to test the yield strength, tensile strength, uniform elongation and elongation at break of the coated ultra-high strength steel substrates of Examples 1-28 and the comparative steel substrates of Comparative Examples 1-4.
[0106] Table 4 lists the mechanical property observation results of the coated ultra-high strength steel substrates of Examples 1-28 and the comparative steel substrates of Comparative Examples 1-4.
[0107] Table 4.
[0108]
[0109]
[0110] Accordingly, in order to verify that the coated ultra-high strength steel of Examples 1-28 prepared by the above steps (1)-(6) has a very good low sensitivity to spot weld cracks, the inventors took samples of the coated ultra-high strength steel of Examples 1-28 and the comparative steel plates of Comparative Examples 1-4 respectively, and conducted spot welding tests on the finished steel plate samples of each example and comparative example. The relevant spot welding process parameters are shown in Table 5 below.
[0111] Table 5 lists the specific spot welding process parameters for the coated ultra-high strength steel of Examples 1-28 and the comparative steel plates of Comparative Examples 1-4.
[0112] Table 5.
[0113]
[0114]
[0115] In the actual spot welding process, one tensile-shear (TSS) specimen, one cross tensile (CTS) specimen, and one metallographic specimen were welded under each welding current. The TSS and CTS specimens were measured by tensile testing machine according to ISO14273-2016 and ISO14272-2016 standards. The results are shown in Table 6 below.
[0116] Accordingly, for the obtained metallographic specimens, the coating on the joint surface was first removed with dilute hydrochloric acid, and the distribution and direction of the spot weld cracks were observed under a microscope. The section passing through the center of the weld nugget and capable of cutting the most spot weld cracks was selected as the metallographic section of the joint. Wire cutting was used for sampling. The section included all welding characteristic areas of the spot weld joint. The sample was then rinsed to prevent foreign matter from interfering with the test results. The rinsed sample was then dried. The dried sample was then mounted, polished, and measured under a metallographic microscope. The maximum crack length was recorded in Table 6.
[0117] Table 6 lists the mechanical properties of the weld joints and the weld joint crack test results of the coated ultra-high strength steels of Examples 1-28 and Comparative Examples 1-4 after spot welding.
[0118] Table 6.
[0119]
[0120] Note: The two values for nominal coating weight in Table 6 refer to the coating weight on the front and back of the steel plate. GI indicates pure zinc coating, GA indicates zinc-iron alloy coating, ZM indicates zinc-aluminum-magnesium coating, and AZ indicates aluminum-zinc coating.
[0121] As can be seen from Table 3 above, the microstructure of the steel substrates of Examples 1-28 and Comparative Examples 1-4 designed in this invention is ferrite + martensite + retained austenite. Furthermore, the microstructure of the substrates of each example and comparative example satisfies the following indicators: the volume ratio of ferrite is 25%–45%, and the volume ratio of martensite is 45%–65%; wherein, the volume percentage of ferrite grains with a size of 10 μm or less is ≥85%, and the volume percentage of ferrite grains with a size of 5 μm or less is ≥55%; the average grain size of retained austenite is ≤2 μm, and the average C content in retained austenite is ≥1.0%.
[0122] As can be seen from Table 4 above, the steel substrates of Examples 1-28 and Comparative Examples 1-4 designed by the invention all have excellent mechanical properties, and their mechanical properties meet the design requirements of the present invention. Specifically, the yield strength of the coated ultra-high strength steel substrates of Examples 1-28 is between 755 and 845 MPa, its tensile strength is between 1040 and 1140 MPa, its uniform elongation is between 14.7 and 16.4%, and its elongation at break is between 22.6 and 25.4%.
[0123] As shown in Table 6, for the finished coated ultra-high-strength steel of Examples 1-28 of this invention, when the welding current is less than the spatter current, the weld joints show no spot weld cracks; when the welding current is greater than the spatter current, the longest crack in the weld joint is less than 5% of the plate thickness. However, for the comparative steel plates of Comparative Examples 1-4 designed in this invention, regardless of whether the welding current is greater than the spatter current, the weld joints will show cracks, and the cracks in the spattered weld joints are more severe than those in the non-splashed weld joints, and the ratio of the maximum crack length to the plate thickness is much greater than 5%. This demonstrates that the coated ultra-high-strength steel of Examples 1-28 designed using the technical solution of this invention has excellent low spot weld crack sensitivity while ensuring the performance of the plate.
[0124] It should be noted that the combination of the technical features in this case is not limited to the combination methods described in the claims of this case or the combination methods described in the specific embodiments. All technical features described in this case can be freely combined or combined in any way, unless they contradict each other.
[0125] It should also be noted that the embodiments listed above are merely specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and similar changes or modifications made thereto are those that can be directly derived or easily conceived by those skilled in the art from the content disclosed in the present invention, and should all fall within the protection scope of the present invention.
Claims
1. A coated ultra-high strength steel with low spot weld crack sensitivity, comprising a steel substrate and a zinc-containing coating on the surface of the steel substrate, wherein the mass percentage of each chemical element in the steel substrate is: C: 0.10–0.30%; Si: 0.30–0.90%; Mn: 1.00–2.20%; B: 0.001–0.003%; Al: 0.30–1.00%; balance is Fe and unavoidable impurity elements; The microstructure of the steel substrate is ferrite + martensite + retained austenite, wherein the volume ratio of ferrite is 25% to 45%; the volume ratio of martensite is 45% to 65%, wherein in the ferrite, the volume ratio of grains with a size of less than 10 μm is ≥85%, and the volume ratio of grains with a size of less than 5 μm is ≥55%. When spot welding is used, if surface cracks occur at the weld point, the maximum length of the surface crack is less than 5% of the plate thickness.
2. The coated ultra-high strength steel as described in claim 1, characterized in that, The mass percentage content of each chemical element in the steel substrate satisfies at least one of the following conditions: C:0.15~0.20%; Si: 0.40–0.80%; Mn: 1.00~2.00%; B:0.0015~0.003%。 3. The coated ultra-high strength steel as described in claim 1, characterized in that, The steel substrate also contains Mo: 0.10-2.00%.
4. The coated ultra-high strength steel as described in claim 3, characterized in that, The Mo mass percentage of the steel substrate is 0.10 to 1.00%.
5. The coated ultra-high strength steel as described in claim 1, characterized in that, The mass percentage of unavoidable impurity elements in the steel substrate satisfies the following conditions: P≤0.01%, S≤0.005%.
6. The coated ultra-high strength steel as described in claim 1, characterized in that, The average C content in the retained austenite is ≥1.0%.
7. The coated ultra-high strength steel as described in claim 1, characterized in that, The average grain size of the retained austenite in the microstructure of the steel substrate is ≤2μm.
8. The coated ultra-high strength steel as described in claim 1, characterized in that, Its mechanical properties meet the following requirements: its yield strength is 600MPa~850MPa, its tensile strength is 980MPa~1150MPa, its uniform elongation is not less than 13%, and its elongation at break is not less than 15%.
9. The coated ultra-high strength steel as described in claim 1, characterized in that, Its coating is a pure zinc coating, a zinc-iron alloy coating, a zinc-aluminum-magnesium coating, or an aluminum-zinc coating.
10. The method for manufacturing coated ultra-high strength steel according to any one of claims 1-9, characterized in that, Including the following steps: (1) Smelting and thin-plate continuous casting; (2) Heating; (3) Hot rolling: The thickness of the oxide scale on the surface of the hot-rolled steel strip is controlled to be ≤4μm, and the mass percentage of FeO+Fe3O4 in the oxide scale on the surface of the hot-rolled steel strip is ≤50wt%; (4) Pickling, or pickling + cold rolling; (5) Continuous annealing: Anneal at 800-920℃, then slowly cool to 700-770℃ at a cooling rate of 3-10℃ / s; then rapidly cool to 200-300℃ at a cooling rate of 50-500℃ / s; then heat to 360-460℃ and hold for 50-600s; finally cool to room temperature; (6) Apply a zinc-containing coating.
11. The manufacturing method as described in claim 10, characterized in that, In step (1), the slab thickness at the exit end of the thin strip continuous casting is controlled to be 50-58 mm.
12. The manufacturing method as described in claim 10, characterized in that, In step (1), the casting speed of the thin strip is controlled to be 2 to 5 m / min.
13. The manufacturing method as described in claim 10, characterized in that, In step (2), the slab is heated to 1200-1250°C.
14. The manufacturing method as described in claim 10, characterized in that, In step (3), the final rolling temperature is controlled at 860-930℃ and the coiling temperature is controlled at 450-600℃.
15. The manufacturing method as described in claim 10, characterized in that, In step (4), when pickling and cold rolling are used, the cold rolling deformation is controlled to be 40% to 60%.
16. The manufacturing method as described in claim 10, characterized in that, In step (5), the volume content of hydrogen in the reducing atmosphere inside the continuous annealing furnace is controlled to be 10-15%.
17. The manufacturing method as described in claim 10, characterized in that, The annealing process parameters in step (5) must satisfy at least one of the following: The annealing temperature is 820–870℃; Slowly cool to 700-730℃ at a cooling rate of 3-10℃ / s; Cool quickly to 250-300℃; Cool quickly and then reheat to 400-430℃, hold for 180-300 seconds.
Citation Information
Patent Citations
Galvanized high-strength steel resistance spot welding method with good joint performance
CN108015401A
Multilayer steel and method of reducing liquid metal embrittlement
CN109385515A
Zinc-coated steel sheet with high resistance spot weldability
CN110892087A
Hot-dip galvanized steel and manufacturing method thereof
CN114807737A
High-strength hot-dip galvanized steel sheet superior in spot weldability and formability
JP2007146246A